An island of constancy in a sea of change: Rethinking project temporalities with long-term megaprojects. Issue 7 (October 2017) - Brookes, Naomi; Sage, Daniel; Dainty, Andrew; Locatelli, Giorgio; Whyte, Jennifer
Abstract: This paper examines the organizational phenomena of long-term projects. While research literature frames projects as "temporary organizations", megaprojects have long initiation and delivery phases, lasting years sometimes decades, and deliver capital assets that are used for decades or centuries. Instead of short-duration activity within a fixed organizational context, these projects involve multiple temporalities, combining more and less temporary forms of organizing in the process of enactment. Using an example of a long-term infrastructural megaproject, a wind-farm, to illustrate the phenomenon, we contribute by articulating different temporalities associated with the delivery project, life-cycle; stakeholder organizations that set up the project; and special purpose vehicles through which it is delivered. Implications of these temporalities for project management research and practice are discussed with reference to understandings of risk and knowledge. We argue that focus on long-term projects and their multiple temporalities opens up new ways of thinking about projects as temporary organizations. Highlights: Examines the organizational phenomena of long-term projects. Articulates how these projects involve multiple temporalities. In them, the project, stakeholders and special purpose vehicles differ temporally. The project may outlive owner and delivery firms; end dates may be negotiated. Focus on multiple temporalities offers new insight for researchers and practitioners.